The makings of meanings: the evaluation of an employment programme for drug-using offenders - Burlison, Paul (2003)
This thesis is based on a case study of the evaluation of an employment programme for drug-using offenders. Initially, my involvement was that of a studentship-funded research assistant, undertaking the associated duties and expectations of that role and working to an already agreed evaluation design. This design can be broadly categorised as quantitative, longitudinal, and summative. Subsequently, my role evolved, as did the evaluation methodology itself, becoming underpinned by Patton's notion of Utilisation Focus', and infused by the, what was initially unarticulated, constructivist hesitation I brought to the endeavour. The findings from the evaluation, which relate to direct Project outputs, staff and service user satisfaction, and service user motivation to participate in the evaluation, are presented. Primary intended user' response to these, as well as the evaluation itself, are gauged from interviews undertaken after a reading of the evaluation final report. I then consider what this case study of one evaluation might tell us about the art of evaluation itself. What might be the lessons for valuation which could be useful for others